Pengaruh Jenis dan Konsentrasi Pupuk Organik Cair Terhadap Pertumbuhan dan Hasil Tanaman Kailan (Brassica Oleraceae L.) dengan Sistem Hidroponik Substrat - Dewi Masitoh; Gatot Subroto (Jember University Press, 2023)
In Indonesia, kailan plants are classified as new plants but have quite large prospects, however, kailan production in Indonesia is still relatively low and is not comparable to the increasing demand for kailan and the availability of agricultural land which is still limited. The use of liquid organic fertilizer with the application of a substrate hydroponic cultivation system is a good alternative in a cultivation system to increase yields in terms of quality and quantity. It is necessary to do research on the effect of the right type and concentration of liquid organic fertilizer for kailan plants. This study aims to determine the effect of the right type of liquid organic fertilizer and the concentration of good liquid organic fertilizer on the yield of kailan plants. The research was conducted in August-October 2022 which took place in Patrang, Jember Regency. This study used the RAL method (Completely Randomized Design) which was arranged in a factorial manner consisting of 2 treatment factors which were applied to kailan plants which were repeated 3 times. The first factor is the type of liquid organic fertilizer (P), which consists of three levels, namely: Rabbit Urine (P1), Nasa (P2), and Cow Biourine (P3). The second factor was the concentration of liquid organic fertilizer (K) which consisted of 4 levels, without POC treatment (K0); 10 ml/l water (K1); 20 ml/l water (K2); 30 ml/l water (K3); 40 ml/l water (K4). The data obtained will be analyzed using analysis of variance (ANOVA). Treatments with significantly different effects were further analyzed using Duncan's test at the 5% level. Based on the data and discussion of the research that has been done, it can be concluded that the best type of liquid organic fertilizer concentration treatment is the Nasa liquid organic fertilizer type treatment, while the more efficient liquid organic fertilizer concentration treatment used to be applied in the kailan cultivation system is the kailan plant treatment. concentration of liquid organic fertilizer 30ml/L. There is an interaction between the types of liquid organic fertilizer treatment at the concentration level of liquid organic fertilizer on the plant wet weight parameter.